2010
DOI: 10.1002/edn.158
|View full text |Cite
|
Sign up to set email alerts
|

Practice nurses’ role and knowledge about diabetes management within rural and remote Australian general practices

Abstract: Background: The increasing prevalence of diabetes and obesity represents a significant disease burden in Australia. Practice nurses (PNs) play an important role in diabetes education and management. Aim: To explore PNs' roles, knowledge and beliefs about diabetes education and management in rural and remote general practice in Australia. Method: Exploratory study undertaken in three phases: 1) Pilot study to test the performance of the questionnaire; 2) One-shot cross-sectional survey using self-complete quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Unlike previous studies which focused on a particular category of HCPs [17]- [20], the current study is unique as our sample included most categories of HCPs with different specialties and backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous studies which focused on a particular category of HCPs [17]- [20], the current study is unique as our sample included most categories of HCPs with different specialties and backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent emphasis on the need for "interdisciplinary teams and "totalcare management" in which all categories of HCPs must directly coordinate and plan care for diabetic patients [17], many of the existing studies related to attitudes of HCPs toward diabetes were limited to one category of HCPs such as physicians [18], pharmacists [17]- [19] and nurses [20] with little focus on the role of dietitians. Hence, this study attempts to assess attitudes of all HCPs related to diabetes and compare those attitudes among subgroups of HCPs.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate knowledge of medication has been found among American and Jordanian nurses (Gerard, Griffin, & Fitzpatrick, 2010;Yacoub et al, 2014) and insufficient knowledge of insulin treatment among 27% of Pakistani registered nurses (RNs) (Ahmed, Jabbar, Zuberi, Islam, & Shamim, 2012). Australasian studies found that some 50% of participating nurses did not know that neuropathy, nephropathy, erectile dysfunction, cardiovascular and cerebrovascular diseases were associated with diabetes (Daly, Arroll, Sheridan, Kenealy, & Scragg, 2014;Livingston & Dunning, 2010). Studies in the United State (US) and United Kingdom (UK) also indicated RNs needing further training in blood glucose monitoring (BGM) (Gerard et al, 2010;Nash, 2009), as was also the case for 75.1% of Nigerian nurses (Oyetunde & Famakinwa, 2014).…”
mentioning
confidence: 99%
“…). It is therefore vital for the HCPs to continually increase their skill and knowledge specific to diabetes, because the formal education they have received about diabetes care may not be adequate (Livingston & Dunning ) to manage complex diabetic presentations. Having specific skills is necessary to complement each other's roles (Gucciardi et al.…”
Section: Discussionmentioning
confidence: 99%